Tingkat Kepuasan Masyarakat Terhadap Pelayanan Perijinan Pemerintah Kota Kupang - Frits Fanggidae; Frans Nyong (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2016)
Public service is one of the absolute government functions implemented. The success indicators of public services provided by the government is, people's satisfaction of the service. Therefore, through KEPMENPAN No. 25/2004, the government established General Guidelines for Preparation of Public Satisfaction Index, Government Agencies Services Unit, with the aim of knowing how much the level of community satisfaction with services provided by the government, measuring about: service procedures, service requirements, clarity of service personnel, service personnel discipline, responsibility of service personnel, the ability of service personnel, speed of service, justice in service, the decency of service personnel, reasonableness of fees, service charges certainty, the certainty of the service schedule, environmental comfort, and security services. Conceptually, there are five principles that must be observed in order to achieve the service quality, namely: tangible, reliable, responsiveness, assurance and empathy. The level of community satisfaction towards services permits issued by SKPD in the Government of Kupang City, as measured by the five principles of quality service to fourteen elements of the people’s satisfaction shows that, the level of community satisfaction with services permits issued by SKPD in the Government of Kupang City, has varying degrees, both in view of the elements of society and the satisfaction of the five principles of quality service. This proves that, the issue of public satisfaction with public services cannot be merely viewed from one aspect, but are complex and multi-dimensional. Thus, to increase community satisfaction with services provided by the government, must be done comprehensively, both from the physical and non-physical aspects, in a sense, is not just a question of the completeness of infrastructure or the speed and ease of service, but also aspects of the attitudes and behavior of officers in giving service.